Arquiteturas do poder: cultura escolar e identidade no Grupo Escolar José Tavares (Queimadas-PB, 1935-1940) - Rodrigues , Taynnã Valentim (2019)
This study embarks upon the roads of Education History under the light of worries stemming from the thinking perspective of the School Group José Tavares in Paraíba during the period from 1935 to 1940, as the result of established dialogues with political projects turned to the educational space. For this purpose, we dialogued with the political conjuncture which reverberated in the State during the aforementioned period, a moment in which the Argemirismo reigned. Within this temporal cut it is possible to notice the existence of political projects with interests directed to primary education, in relation to the fabrication of a national and regional identity, which we can call brasilidade and parabanidade. Such projects gained corporeity in the structure of the School Groups. To make this discussion, it was used as reference Pinheiro‟s interpretation (2002), which highlighted the moment of bigger School Groups‟ constructions in Paraíba such as Período de Euforia. We also used Jorge Nagle‟s reading (2001) in realtion to Entusiasmo pela Educação and Otimismo Pedagógico, and Marta Maria Chagas de Carvalho (1998) that did a reflection on the educational institution as a civic mold ready to shape the population within the governmental interests. This work is also allied to the narratives of Aluízio Araújo. He gave his student experiences in the School Group José Tavares, institution that was bron from the context of the discussion to which this research stems from. Mr. Aluízio‟s memories reveal traces of the School Culture surrounding by the Project of brasilidade and paraibanidade. Besides the pertinent bibliography, methodologically the current dissertation is made linked to the documental analysis of Messages and Reports of the government of Paraíba, school files, Union Journal, School Review, and finally, Aluízio Araújo‟s memories.